Phylogeography and Population Demography of Parrotia subaequalis, a Hamamelidaceous Tertiary Relict ‘Living Fossil’ Tree Endemic to East Asia Refugia: Implications from Molecular Data and Ecological Niche Modeling - Yunyan Zhang; Zhiyuan Li; Qixun Chen; Yahong Wang; Shuang Wang; Guozheng Wang; Pan Li; Hong Liu; Pengfu Li; Chi Xu; Zhongsheng Wang (Plants, 2025)
The diverse topography and mild monsoon climate in East Asia are considered to be important drivers for the long-term ecological success of the Tertiary relict ‘living fossil’ plants during the glacial/interglacial cycles. Here we investigated the phylogeographic pattern and demographic history of a hamamelidaceous Tertiary relict ‘living fossil’ tree (Parrotia subaequalis) endemic to the subtropical forests of eastern China, employing molecular data and ecological niche modeling. In the long evolutionary history, P. subaequalis has accumulated a high haplotype diversity. Weak gene flow by seeds, geographical isolation, and heterogeneous habitats have led to a relatively high level of genetic differentiation in this species. The divergence time of two cpDNA lineages of P. subaequalis was dated to the late Miocene of the Tertiary period, and the diversification of haplotypes occurred in the Quaternary period. Paleo-distribution modeling suggested that P. subaequalis followed the pattern of ‘glacial expansion-interglacial compression’. The Dabie Mountain and Yellow Mountain in Anhui Province and the Tianmu Mountain and Simin Mountain in Zhejiang Province were inferred to be multiple glacial refugia of P. subaequalis in East Asia and have been proposed to be protected as ‘Management Units’. Collectively, our study offers insights into the plant evolution and adaptation of P. subaequalis and other Tertiary relict ‘living fossil’ trees endemic to East Asia refugia.